Essential rehabilitation services in a rural setting using patient and family centred care model: a case report - Rao K., Arun; Thomas, Susan; Narayan, Vivek (International Journal Of Community Medicine And Public Health, 2018)
Chronic diseases have a significant social and economic effect on individuals and societies. These diseases require lifelong care and management. Individuals with chronic diseases need to focus on complications, treatment and prevention. Self-efficacy for performing self-care behaviours is important to bring a change in lifestyle in these individuals which will eventually help in successful personal disease management. This case discusses a typical patient and family centerd care (PFCC) model where the lifestyle changes of a 14-year-old male hemophilia patient were successfully managed. This hemophilia patient required constant medical services, however there were constraints like low accessibility and affordability to healthcare centers. In this model, patients and family members are made partners and collaborators in delivering a sustainable focus on the patient. This model has helped in reducing the frequency of hospital visits and caretakers valuable time. Patient and family-centered care enables patients to self-manage treatment and facilitate doctors to attend other critical cases efficiently. The implementation of PFCC in managing a hemophilia patient turned out to be immensely useful and thus could improve the patient’s quality of life.